Frailty phenotype in heart failure: A condition that transcends age - Valdiviesso, Rui (2023)
Introduction and objectives: Studies on younger frail and pre-frail subjects suffering from heart failure (HF) are scarce, except for those focusing on the critically ill. This work aims to describe differences between younger (<65 years) and older (>= 65 years) pre-frail and frail HF outpatients regarding their nutritional, functional and clinical statuses.Methods: In this cross-sectional study, a sample of 99 HF frail and pre-frail patients (aged 24-81 years, 38.4% women, 21.2% frail, 59.6% <65 years) was recruited from an HF outpatients' clinic in northern Portugal. Muscle mass was estimated from mid-upper arm muscle circumference. Weight status was assessed using body mass index. Hand grip strength and gait speed were measured. Medical records were reviewed. Associations between participants' characteristics and age were calculated using binary logistic regression.Results: Age was associated with hand grip strength (OR=0.90), gait speed (OR=0.01) and dia-betes (OR=4.95). Obesity, muscle mass or heart failure functional classes were not associated with age categories.Conclusion: There is an overall lack of differentiation between younger and older HF patients with the frailty phenotype. Therefore, frailty phenotype should be assessed in all patients, regardless of age. Hand grip strength seems to be a good predictor for older age and more studies are needed to define age-specific hand grip strength cut-offs for HF populations. (c) 2023 Sociedade Portuguesa de Cardiologia. Published by Elsevier Espan similar to a, S.L.U. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).